The mental aspect of house keeping - Marty, Freide E. (My University, 1905)
Introduction: Some one has said, “keep house in order to live comfortably, don’t live in order to keep house.” The advance of society rests on the personal health, sanity and happiness of its members, whose bet growth require quiet comfortable homes; with peace and health order and beauty. Upon the house keeper lays the responsibility of providing such conditions together with good wholesome nourishing food. Innumerable theories have been advanced as regards methods and management of house hold duties but there are none of us that can select one particular plan and execute our tasks according to its specific guidance. Each housekeeper is compelled to outline a system of work according to her own environments.
Citation: Marty, Freide E. The mental aspect of house keeping. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Comfort of Household; Household Economy; Cheerful Spirit; Theses; Manuscripts (documents)